A New Approach to Microgrids: Interaction Between Single-Phase and Three-Phase Four-Wire Generation with Unbalanced Loads - Lopez-Villarroel, M; Espina-Gonzalez, E; Diaz-Diaz, M; Pizarro-Jimenez, P; Ravet-Orellana, T; Plitt-Morales, M (Institute of Electrical and Electronics Engineers Inc., 2024)
The advantages that microgrids can deliver and manage within the current electrical grid are well known, and various methodologies and algorithms have been proposed. However, by focusing on the application of a real electrical system, these studies fail to consider simultaneous single-phase and three-phase generation operation, as well as an unbalanced system. Therefore, this paper proposes a distributed secondary control strategy that addresses these previously unexamined topics, ensuring reliable and safe operation. Thus, a microgrid with six single-phase agents per phase plus a three-phase agent with unbalanced loads is modeled, which allows corroborating the interaction between these agents in a non-ideal system thanks to several simulation results that validate the proposed strategy and open the door to broaden the scope of this type of applied research. © 2024 IEEE.